Tuning the deposition of molecular graphene nanoribbons by surface functionalization - Konnerth, R.; Cervetti, C.; Narita, Akimitsu; Feng, Xinliang; Muellen, K.; Hoyer, A.; Burghard, M.; Kern, K.; Dressel, Martin; Bogani, Lapo (Nanoscale, 2015)
We show that individual, isolated graphene nanoribbons, created with a molecular synthetic approach, can be assembled on functionalised wafer surfaces treated with silanes. The use of surface groups with different hydrophobicities allows tuning the density of the ribbons and assessing the products of the polymerisation process.
CRIS-Team Scopus Importer:2023-03-20